Cervical length and quantitative fetal fibronectin in the prediction of spontaneous preterm birth in asymptomatic women with congenital uterine anomaly - Ridout,AE; Ibeto,L; Ross,G; Cook,JR; Sykes,L; David,AL; Seed,PT; Tribe,R; Bennett,PR; Terzidou,V; Shennan,AH; Chandiramani,M; et al. (American Journal of Obstetrics and Gynecology, 2019)
BACKGROUND: Congenital uterine anomalies (CUA) are associated with late miscarriage and spontaneous preterm birth (sPTB). OBJECTIVES: Our aim was to 1) determine the rate of sPTB in each type of CUA and 2) assess the performance of quantitative fetal fibronectin (qfFN) and transvaginal cervical length (CL) measurement by ultrasound in asymptomatic women with CUA for the prediction of sPTB at <34 and <37 weeks of gestation. STUDY DESIGN: This was a retrospective cohort of women with CUA asymptomatic for sPTB, from four UK tertiary referral centres (2001-2016). CUAs were categorised into fusion (unicornuate, didelphic and bicornuate uteri) or resorption defects (septate, with or without resection and arcuate uteri), based on pre-pregnancy diagnosis. All women underwent serial transvaginal ultrasound CL assessment in the second trimester (16 to 24 weeks' gestation); a subgroup underwent qfFN testing from 18 weeks' gestation. We investigated the relationship between CUA and predictive test performance for sPTB before 34 and 37 weeks' gestation. RESULTS: Three hundred and nineteen women were identified as having CUA within our high-risk population. 7% (23/319) delivered spontaneously <34 weeks, and 18% (56/319) <37 weeks' gestation. Rates of sPTB by type were: 26% (7/27) for unicornuate, 21% (7/34) for didelphic, 16% (31/189) for bicornuate, 13% (7/56) for septate and 31% (4/13) for arcuate. 80% (45/56) of women who had sPTB <37 weeks did not develop a short CL (<25 mm) during the surveillance period (16-24 weeks). The diagnostic accuracy of short CL had low sensitivity (20.3) for predicting sPTB <34 weeks. Cervical Length had ROC AUC of 0.56 (95% CI 0.48 to 0.64) and 0.59 (95% CI 0.55 to 0.64) for prediction of sPTB <34 and 37 weeks' respectively. The AUC for CL to predict sPTB <34 weeks was 0.48 for fusion defects (95% CI 0.39 to 0.57) but 0.78 (95% CI 0.66 to 0.91) for women with resorption defects. Overall quantitative fetal fibronectin had